2014
DOI: 10.1183/09031936.00115514
|View full text |Cite
|
Sign up to set email alerts
|

High positive predictive value of Xpert in a low rifampicin resistance prevalence setting

Abstract: Although drug susceptible tuberculosis (TB) is a curable disease, spread of rifampicin-resistant TB, including multidrug-resistant (MDR)-and extensively drug-resistant (XDR)-TB, is a threat to disease control worldwide [1] While the World Health Organization (WHO) has endorsed the use of Xpert for TB diagnosis as a replacement for sputum smear examination [6], concerns have been raised about the low positive predictive value (PPV) of rifampicin-resistant Xpert results in patients who have never previously been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Those authors also demonstrated that 82% of the rifampin-resistant cases detected by the Xpert MTB/RIF test were confirmed as cases of multidrug-resistant tuberculosis in a phenotypic sensitivity test. 30 Therefore, although our sample might not have been representative of the true proportion of resistance in the state, the detection of rifampin resistance in 8.8% of the cases indicates that the Xpert MTB/RIF test can facilitate the early identification of cases of multidrug-resistant tuberculosis in Brazil.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Those authors also demonstrated that 82% of the rifampin-resistant cases detected by the Xpert MTB/RIF test were confirmed as cases of multidrug-resistant tuberculosis in a phenotypic sensitivity test. 30 Therefore, although our sample might not have been representative of the true proportion of resistance in the state, the detection of rifampin resistance in 8.8% of the cases indicates that the Xpert MTB/RIF test can facilitate the early identification of cases of multidrug-resistant tuberculosis in Brazil.…”
Section: Discussionmentioning
confidence: 91%
“…The Xpert MTB/RIF test has high specificity for the detection of rifampin resistance (98%), already well established in previous studies. 6 , 29 Trajman et al 30 showed that the test has a high positive predictive value for rifampin resistance (90.2%), even in countries where the prevalence of drug-resistant tuberculosis is relatively low. Those authors also demonstrated that 82% of the rifampin-resistant cases detected by the Xpert MTB/RIF test were confirmed as cases of multidrug-resistant tuberculosis in a phenotypic sensitivity test.…”
Section: Discussionmentioning
confidence: 99%
“…Quality bacteriological diagnosis includes the WHO-recommended rapid (molecular) assays [12,[41][42][43][44][45][46]; it should be done as early as possible (ideally initiated on the day the presumed patient is identified) within evidence-based diagnostic algorithms and guidelines. Currently available genotypic methods are the automated real-time nucleic acid amplification technology for rapid and simultaneous detection of Mycobacterium tuberculosis and rifampicin resistance (e.g.…”
Section: Notesmentioning
confidence: 99%
“…Determined by previous study 4 , RMT-TB has high specificity in detecting resistance to rifampicin (98%). Another investigation 27 showed the high positive predictive value for resistance to rifampicin (90.2%) in countries where the prevalence of tuberculosis is low. In addition, it also demonstrated, that 82% of the cases of resistance to rifampin diagnosed using RMT-TB were subsequently confirmed as cases of drug-resistant tuberculosis.…”
Section: Discussionmentioning
confidence: 99%